2017
DOI: 10.3892/etm.2017.4047
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-131 therapy alters the immune/inflammatory responses in the thyroids of patients with Graves' disease

Abstract: Abstract. The aim of the present study was to evaluate the serum levels of interleukin-6 (IL-6), CXC chemokine ligand-10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…This difference in results may be attributed to the fact that subsequent RAI therapy may evoke a different immunological response. 2 In the present paper, TRAb at baseline level correlated with 4 h, 24 h and 48 h RAIU, confirming the immunological origin of GD. This finding proves that RAIU and thyroid scanning still enable a definitive assessment of thyroid physiology.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This difference in results may be attributed to the fact that subsequent RAI therapy may evoke a different immunological response. 2 In the present paper, TRAb at baseline level correlated with 4 h, 24 h and 48 h RAIU, confirming the immunological origin of GD. This finding proves that RAIU and thyroid scanning still enable a definitive assessment of thyroid physiology.…”
Section: Discussionsupporting
confidence: 83%
“…1 In view of a significant reduction of ThV after RAI therapy, one question worth considering is the influence of the therapy on the final level of anti-thyroid antibodies (ATA). 2,3 Another issue to examine is the possible relationship between the level of ATA and radioiodine turnover, specifically the tracer uptake, radioactive iodine uptake -RAIU and thyroidal 131 I effective half-life (EHL). 4 The connection of these factors with the use of steroid protection and the potential subsequent dose of thyroid replacement therapy (TRT) due to post-therapeutic hypothyroidism is another issue to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…The CDC has indicated that patients with bone marrow suppression are at higher risk for COVID-19 severity and complications (US Department of Health & Human Services 2020). I 131 itself can modulate the immune system with cytokines dysregulation observed following I-131 treatment for Graves' disease (Du et al 2017). In those thyroid cancer patients with thyroid autoimmunity, treatment with I 131 can increase IL-6, a cytokine implicated in severe respiratory disease and death from COVID-19.…”
Section: Predilection For Thyroid Cancer In Covid-19 Patientsmentioning
confidence: 99%
“…Several issues concerning the impact of DTC treatment on COVID-19 outcome await clarification. First, a cautious patient selection for RAI treatment might be essential in the COVID-19 era due to the potential RAI-driven attenuation of immune responses in parallel with the concern about the safety/efficacy balance of RAI for most intermediate-risk and low-risk subgroups of (D)TC [ 121 , 122 , 123 ]. Second, whether L-T4 binding to integrin αvβ3 can diminish the integrin αvβ3-mediated internalization of the SARS-CoV-2 is yet to be investigated.…”
Section: Future Perspectivesmentioning
confidence: 99%